Estratégias para aumento da concentração de progesterona durante o desenvolvimento do folículo ovulatório em vacas holandesas em lactação submetidas à inseminação artificial em tempo fixo - Albuquerque, João Pedro de [UNESP] (2015)
The present study evaluated if P4 concentration during ovulatory follicle development in a timed artificial insemination (TAI) protocol based on P4/E2 affects pregnancy per AI in lactating Holstein cows. Our hypothesis is that cows that present higher P4 concentration at PGF2α administration have also higher fertility. To alter P4, animals (n=594) were randomly assigned to receive one or two intravaginals devices of P4 (CIDR®, Zoetis, SP, Brazil). TAI protocol utilized was: d-11 intravaginal device of P4 (new or previously used by 9 days) + 2mg im EB (Gonadiol®, Zoetis, SP, Brazil) + 100mcg im GnRH (Cystorelin®, Merial, SP, Brazil); d-4, 25mg im Dinoprost (Lutalyse®, Zoetis, SP, Brazil); d-2, 25mg im Dinoprost + 1mg im ECP (ECP®, Zoetis, SP, Brazil) + CIDR removal; d0, TAI. Animals in the group 2CIDR received an adicional CIDR at d-11, which was removed at d-4. At d-11 (n=117), d-4 (n=351), d0 (n=214) and d10 (n=72), blood samples were taken from cows for P4 concentration measurements. Pregnancy per AI was determined by ultrasound at d32 (DG1) and d60 (DG2). The binomial data were analyzed using PROC GLIMMIX and continuous data using PROC MIXED of SAS. An effect was considered significant when P<0.05 and tendency when P<0.1. P4 did not differ among treatments at d-11 (1CIDR=4.2±0.4ng/ml; 2CIDR=4.5±0.4ng/ml; P>0.1), and at d-4 (1CIDR=3.5±0.2ng/ml; 2CIDR=3.8±0.2 ng/ml; P>0.1). An interaction was detected between treatment and CL presence at the beginning of TAI protocol in P4 at d-4 (without CL and 1CIDR=2.7±0.3ng/ml; 2CIDR= 3.6±0.3ng/ml, with CL and 1CIDR=4.3±0.3ng/ml; 2CIDR= 4.0±0.3ng/ml; P<0.05). There was no difference among treatments in pregnancy per AI and pregnancy loss between DG1 and DG2 [DG1: 1CIDR= 20,0% (81/310) vs. 2CIDR= 15,7% (65/284); DG2: 1CIDR= 18,2% (74/310) vs. 2CIDR= 13,8% (57/283); Pregnancy loss: 1CIDR= 14,1% (7/81) vs. 2CIDR= 11,5% (7/64); P>0,1]. 37,0% (28/63)...